By-Products from Rice as Fillers in Natural Rubber - มูลชัย ดริญญา (KKU Science Journal, 2012)
This article presents knowledge and research on three by-products from rice as fillers in natural rubber, including rice husk, rice husk ash and defatted rice bran. Rice husk is the outer layer of rice grain which is removed during rice processing. Rice husk ash is a by-product from the burning of rice husk. Rice bran is a major by-product obtained from the polishing process that produces white rice. Rice bran oil is extracted from rice bran, leaving defatted rice bran as by-product. The discussion focuses on the effects of by-products from rice on the properties of natural rubber vulcanisates. The properties of natural rubber vulcanisates are affected by the rubber-filler interaction, particle size and specific surface area of the fillers. In addition, the properties of by-product from rice-filled vulcanisates are also compared with traditional filler-filled vulcanisates.